Managing the transition from farmers’ groups to agricultural cooperatives in Lao PDR - Castella, J.C.; Bouahom, B.; Keophoxay, Anousith; Douangsavanh, L. (2011)
In a time of transition from subsistence to commercial agriculture, small farming households need to be better organized in order to match the market demand in terms of product volume and quality. However, spontaneous initiatives are often discouraged by the lack of proper support in terms of credit, infrastructures, legal framework or relevant information. After a period of collectivization, then the dismantlement of former State-cooperatives, the recent legislation related to farmers associations and agricultural cooperatives is difficult to translate into concrete collective action. Active informal associations in Laos tend to be credit groups or small income generating groups. Small farmers’ groups and agro-enterprises have been created - in most cases with the help of international projects - that could lay the foundation of future cooperatives. However, policy distortions tend to favor large-scale enterprises and create unfair competition for small agro-enterprises in mobilizing capital. The conditions for the emergence of larger associations or cooperatives from existing groups were investigated. Our study revealed the importance of social networks and power relations as a factor of cohesion within groups. Local leadership plays a crucial role in connecting the group members to the village and district institutions. Recommendations are provided to improve group management rules as a pre-requisite to up-scaling into larger associations, e.g. monitoring and alert system for the compliance of group members and managing committee to the internal rules, reporting procedures to group members, transparency of group decision making processes.